2013
DOI: 10.1542/peds.2012-1427j
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Surgical Outcomes for Adolescents and Young Adults With Inflammatory Bowel Disease

Abstract: OBJECTIVE: To examine whether hospital type (children' s hospital or generalist hospital) and surgeon specialty are associated with variations in surgical outcomes for hospitalized adolescents and young adults with inflammatory bowel disease (IBD) requiring surgery. CONCLUSIONS: Disparate outcomes for adolescents and young adults receiving care in children' s versus generalist hospitals and from different types of surgeons reveal the need to better understand how practice setting and surgical specialty may mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It is worth mentioning that hospital experience in IBD-related surgery was not related to the rate of ePOCs, except for anastomotic leak, which was more common in hospitals with <30 surgeries performed between 2007 and 2010 than in hospitals with >60 surgeries performed during the same time period ( P = 0.001). This finding is similar to that of previous studies, where surgeon experience was associated with better outcomes [22, 23]. In our study, most of the surgeries were performed by specialized colorectal surgeons, thus explaining the low rate of differences found.…”
Section: Discussionsupporting
confidence: 92%
“…It is worth mentioning that hospital experience in IBD-related surgery was not related to the rate of ePOCs, except for anastomotic leak, which was more common in hospitals with <30 surgeries performed between 2007 and 2010 than in hospitals with >60 surgeries performed during the same time period ( P = 0.001). This finding is similar to that of previous studies, where surgeon experience was associated with better outcomes [22, 23]. In our study, most of the surgeries were performed by specialized colorectal surgeons, thus explaining the low rate of differences found.…”
Section: Discussionsupporting
confidence: 92%
“…The highly varied opioid exposure proportion across hospitals after accounting for patient demographic and clinical differences suggests, however, that patients with similar conditions may get different pain management if they go to different hospitals. Hospital-level variations have been reported for many aspects of clinical care and outcomes, such as cesarean delivery proportion, 21 surgical outcomes, 22 and readmission proportion, 23 but few studies reported the hospital-level variations on opioid use patterns among pediatric inpatients. A previous study by members of our research team reported that among 1466 pediatric patients dying from cancer, opioid prescription varied substantially across children's hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous research, children's hospitals were defined according to (i) American Hospital Association (AHA) children's hospital designation; or (ii) institutions that had 10 or more pediatric subspecialties recorded in the database. 19 Hospitals that did not meet this criterion were categorized as general community hospitals.…”
Section: Methodsmentioning
confidence: 99%